PENGARUH MODEL PEMBELAJARAN JIGSAW DAN DISIPLIN BELAJAR SISWA TERHADAP HASIL BELAJAR ILMU PENGETAHUAN SOSIAL (IPS) - Edi Kurniawan; Mulyadi Na (Akademika, 2016)
This research aims to expose and test that: (1) learning social studies between studentswho use learning model Gigantic Jigsaw higher than the social studies lesson with conventionalmodels. (2) There is no effect interaction between models gigantic jigsaw discipline and learnabout the result social studies lesson. (3) There was a difference between social studies lessonusing models gigantic jigsaw higher than that conventional models for the students who havediscipline. (4) There was a difference between social studies lesson that uses a model giganticjigsaw higher than that conventional models for the students who have a discipline is low.Methods in this research uses an experiment with the designs factorial group 2 x 2. Thepopulation in research is all students in grade V SD Air Hangat Timur subdistrict in KerinciRegency Jambi Province. Target population is that the students are primary school of 111/IIIwarm water Koto Tebat sub-district East Kerinci Regency with the number of students 150students, the technique Samples this by random sampling (random simple) divided 2 classesdetermined randomly which grade class treatment and control. The formula for the validity andreliability as follows: correlation points biseral (rpbis) the equation: K-R. 20, The formulaProdak moment Pearson and the formula Alpha Cronbach.Results of research is: Get the Fhitung of 40.040 and values P of 0.000 with Ftabel of1.671 (df = 2), which means that the influence signifikan between there are learning modelGigantic Jigsaw and Discipline students' learning together - to learning social science students.Conclusion, that model of teaching Gigantic Jigsaw and discipline learning effective enough toimprove learning Social Science